Determination and estimation of the glycemic index of selected Malaysian foods - Osman, Nur Maziah Hanum (2015)
Glycemic Index (GI) is used to rank carbohydrate foods based on their ability to raise postprandial blood glucose level after eating. Research on GI testing for Malaysian foods are still at its infancy and its applicability in mixed meals are debatable. Therefore, this experimental study was conducted to determine and estimate the GI of commonly consumed foods in Malaysia including mixed meals. A total of 33 healthy subjects (15 men and 18 women, mean BMI 22 ± 2.25 kgm-2, mean age 23 ± 2 years) were recruited via advertisement throughout Universiti Putra Malaysia. Subjects were divided into three groups namely Rice (Fragrant Rice, Red Rice, and Parboiled Rice), Noodles (Noodles) and Kuih (Keropok Lekor, Cucur Bilis, Cekodok, Wet Spring Roll and Fried Spring Roll) Groups. Besides, mixed meals (Fried Fragrant Rice, Fried Red Rice, Fried Parboiled Rice, Fried Noodles, and Noodles Soup and Spaghetti Soup) were assigned to the subjects from Rice and Noodles Group respectively. Subjects were randomly assigned to the food tested and the three times reference food (glucose solution). Capillary blood glucose was measured before eating and over two hours postprandial. The incremental areas under the blood glucose curve (iAUC) were calculated and GI value of tested foods were measured. All the procedures were adhered to the Australian Standard 2007©. The estimation of GI in mixed meals were calculated using predicted or adjusted techniques. If the GI is a valid measure in estimating the GI in mixed meals, it should provide significant association between measured GI and predicted techniques or measured GI and adjusted techniques. The iAUC of the test foods ranging from 72.15±8.96 to 161.09±15.14 mmol.min/L with Wet Spring Roll yielding the highest, while Fried Parboiled Rice showed the lowest blood glucose response. There was no significant difference were found between the iAUC of each test food and the reference food (202±7.75mmol.min/L) (p<0.05) except for Noodles Group which showed significantly lower than the reference food. Adding fat and protein in mixed meals was further reduced the iAUC by 18 to 36%. There was a significant difference between GI of the tested foods and reference food. Wet Spring Roll has the highest GI value and this were significantly difference to Red Rice, Parboiled Rice, Noodles, Keropok Lekor, Cucur Bilis and Cekodok Pisang (p<0.05). The GI (glucose =100) of the food in descending order were as followed; Wet Spring Roll (GI = 78), Fragrant Rice (GI=65), Fried Spring Roll (GI=63), Red Rice (GI=62), Cucur Bilis (GI=58), Parboiled Rice (GI=57), Keropok Lekor (GI=57), Cekodok Pisang (GI=56) and Noodles (GI=55). Only the adjusted GI was significantly associated with measured GI (r=0.43, p<0.01) but not the predicted GI (p> 0.05). In conclusion, the iAUC of Noodles Group were significantly lower as compared to reference food. Rice, Noodles and Kuih Groups fall into medium GI categories, except for Wet Spring Roll which was categorized into high GI food. Addition of fat and protein into the meal cause a further reduction in iAUC. GI in mixed meals was a valid measure to estimate GI value in mixed meals as it provides significant association between the measured GI in mixed meals and adjusted GI in mixed meals but no significant association found between measured GI in mixed meals and predicted GI in mixed meals.